Effects of a Pre-weaning Socialization System on Piglet Mortality and Growth Performance, and Subsequent Sow Performance - Larissa L. Becker; Paula Giacomini; Jordan T. Gebhardt; Mike D. Tokach; Robert D. Goodband; Joel M DeRouchey; Jason C. Woodworth; Annie B. Lerner (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 3,307 (PIC L 42) mixed-parity sows and 55,160 (PIC 337 × L 42) piglets were used to determine the effects of different farrowing systems on piglet livability, lifetime growth performance, and subsequent sow performance. Treatments were assigned to farrowing rooms and consisted of a conventional farrowing system (sows and piglets housed in individual farrowing crates) or a pre-weaning socialization system (crate dividers removed between farrowing crates and walkways within 6 to 24 hours post-farrowing such that 12 to 32 litters of piglets were co-mingled). A total of 40 farrowing rooms with 80 crates each were used with 20 replications per treatment. Pigs were weaned at approximately 23 d of age. No differences were observed in lactation length, total born, born alive, stillborn, mummies, or the number of pigs weaned. Pre-wean mortality was greater (P < 0.001) for pigs from the pre-weaning socialization system compared to pigs from the conventional system (14.7 vs 12.6%, respectively). A greater (P ≤ 0.015) percentage of pigs died in the pre-weaning socialization system compared to pigs from the conventional system due to being laid on, starving out, Streptococcus suis, and either umbilical or scrotal ruptures. However, a greater (P = 0.014) percentage of pigs died from scours in the conventional system compared to the pre-weaning socialization system. No differences were found in subsequent sow performance, except a marginally significant (P ≤ 0.082) increase in the percentage of sows bred by d 4 and 7 for sows previously housed in the pre-weaning socialization system. A subset of offspring (4,313 pigs initially 11.9 ± 0.34 lb) were transported to a commercial research facility to evaluate lifetime performance. Weaning weights were heavier (P < 0.001) for the conventional system compared to the pre-weaning socialization system. Pigs were housed in pens according to sow treatment (conventional or pre-weaning socialization) with 44 to 46 pigs per pen and 48 replications per treatment. During the nursery and grow-finish periods, pigs from the conventional system had increased (P < 0.001) BW, ADG, ADFI, but poorer F/G compared to pigs from the pre-weaning socialization system. In the nursery phase, removals, mortality, and total removals and mortality were greater (P ≤ 0.059) in pigs raised in the pre-weaning socialization system than in the conventional system, but no differences were observed in the growing-finishing phase. For the overall period (d 23 to 183), pigs from the conventional system had increased (P ≤ 0.001) BW, ADG, and ADFI, but poorer F/ G compared to pigs from the pre-weaning socialization system. No differences were observed for removals and mortality. For overall carcass data, pigs from the conventional system had increased (P ≤ 0.094) HCW, carcass yield, loin depth, and lean percentage compared to pigs from the pre-weaning socialization system. In summary, pigs raised in the conventional farrowing system had increased livability, lifetime growth performance, and carcass characteristics compared to pigs raised in the pre-weaning socialization system.
Keywords: sow; pre-weaning socialization system; pre-weaning mortality